Influence of weather on incidence of bronchiolitis in Australia and New Zealand - Hoeppner, T.; Borland, M.; Babl, F.; Neutze, J.; Phillips, N.; Krieser, D.; Dalziel, S.; Davidson, A.; Donath, S.; Jachno, K.; South, M.; Williams, A.; et al. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Paediatrics and Child Health Division (The Royal Australasian College of Physicians) Aim: We aimed to examine the impact of weather on hospital admissions with bronchiolitis in Australia and New Zealand. Methods: We collected data for inpatient admissions of infants aged 2–12 months to seven hospitals in four cities in Australia and New Zealand from 2009 until 2011. Correlation of hospital admissions with minimum daily temperature, wind speed, relative humidity and rainfall was examined using linear, Poisson and negative binomial regression analyses as well as general estimated equation models. To account for possible lag between exposure to weather and admission to hospital, analyses were conducted for time lags of 0–4 weeks. Results: During the study period, 3876 patients were admitted to the study hospitals. Hospital admissions showed strong seasonality with peaks in wintertime, onset in autumn and offset in spring. The onset of peak incidence was preceded by a drop in temperature. Minimum temperature was inversely correlated with hospital admissions, whereas wind speed was directly correlated. These correlations were sustained for time lags of up to 4 weeks. Standardised correlation coefficients ranged from -0.14 to -0.54 for minimum temperature and from 0.18 to 0.39 for wind speed. Relative humidity and rainfall showed no correlation with hospital admissions in our study. Conclusion: A decrease in temperature and increasing wind speed are associated with increasing incidence of bronchiolitis hospital admissions in Australia and New Zealand.